Lessons from Civil Resistance for the Battle against Financial Corruption. (August 2014) - Ackerman, Peter; Beyerle, Shaazka
The first part of this article presents an overview of civil resistance theory and practice, including key concepts and the historical record of nonviolent movements ending authoritarian and occupying regimes. It will also present a practical checklist for assessing why people power movements succeed or fail. The second part of this article will demonstrate how civil resistance applies to the global scourge of financial corruption. It will first illustrate two recent successful people power campaigns against financial corruption, then examine their dynamics in terms of new research and analysis of organized, collective nonviolent action targeting graft and abuse. Finally, it will adapt the general civil resistance checklist to the anti-corruption arena, concluding with the specific elements that are most critical to curbing financial corruption.